DEVELOPING INDONESIAN LANGUAGE SKILLS AS A PLACE TO EXPRESS CREATIVE IDEAS BY INTROVERTED STUDENTS - Nur Hafidah (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
Every child has special thinking. The spirit to achieve goals manifested from the plan. Efforts to build branding in interpersonally must recognize yourself, control yourself, and be consistent with yourself. The personality type of the human character is not a hindrance. Hone all four types of language skills through listening, reading, writing and speaking. The type of choosing language skills on the personality type of each child's character has a difference. The social environment has a big influence on the priorities of children's thinking in exploring creative ideas. The problems in this research are: 1) How to Develop Indonesian Language Skills as a Place to Express Creative Ideas by Introverted Students? while the objectives of this study are: 1. Develop Indonesian language skills as a place to express creative ideas by students. This study uses R & D research methods, the research model of Baker and Shutz's version. The research is relevant to the researcher's thesis which is related to the research of Maria Eny Kurniati 2016 with the thesis on "Development of Media and Indonesian Language Learning Materials with Microsoft PowerPoints for Class VIII Semester 2 SMP Marganingsih Muntilan Students". The similarities of each of these studies are both using the Research and Development method and using the Baker and Shutz research model. The difference lies in the research conducted by researchers, namely articles, while the relevant research is in the form of a thesis.